Some general thoughts on tense and aspect in Modern Greek - Bielecki, Robert; Trąba, Kamil (Lingua Posnaniensis, 2018)
The morphological categories belonging to the semantic dimension of Tense in Modern Greek, as it is traditionally conceived, seem to be distinguished by means of non-homogeneous criteria. In this paper the temporal and aspectual meanings are treated separately. In consequence, Modern Greek has at its disposal (i) six Tenses and (ii) two Aspects. The meanings of the six Tenses are captured systemically by means of three Time-points: (i) Event Time, (ii) Reference Time and (iii) Speech Time, which are referred to each other in the order given by means of the relations of (i) previousness and (ii) simultaneity. In turn, the meanings of the two Aspects are captured by means of the notions of (i) Shortness and (ii) Longness, which are identified as the bedrock of the aspectual oppositions in Modern Greek. Other aspectual meanings such as Termination, Inchoativity, Completion, etc. are conveyed by the lexical stems of the appropriate verbs linked with the affixal markers of the two Aspects.